Autism Service Center (ASC) Management: Role of Government Service for Autism Spectrum Disorder (ASD) Children - Baghiroh, Raeh Niken; Sugiyo, Sugiyo; Deliana, Sri Maryati (Universitas Negeri Semarang, 2020)
Based on the data from (klinikautis.com), the number of children with Autism Spectrum Disorder (ASD) in Indonesia increases by up to 134.000. Therefore, the government established a special program to take care of ASD children, namely Autism Service Center (ASC). ASC is a place for children who have psychological and physical disorders to get special education. The results of observation shows that many ASD children of Early Childhood Education in Blitar City were not handled well. The research aims to describe and analyze more deeply about the ASC program management as well as the inhibiting and supporting factors in the implementation of the ASC program in Blitar City. This research applied a qualitative research approach with a case study design. The data collection techniques used were observation, interview, and document study. The subjects of this research were the head of the ASC, educators/therapists, program implementing assistants, and students and their parents. Source and method triangulation were applied to check the validity. The data analysis was done through data reduction, data presentation, and conclusion drawing. The results showed that the management which consisted of planning, organizing, implementing, and controlling had been carried out systematically and efficiently. The inhibiting factors in the implementation of the program were parents who were less disciplined in selecting dietary for their children, home program was not run properly, and the time span of therapy was very short. Whereas the supporting factors were the supports from other agencies for the ASC program, the educators/therapists were capable in their field of expertise, and parents’ active-participation in parenting to increase their knowledge in taking care of ASD children.